2022
DOI: 10.1016/j.jbc.2022.101627
|View full text |Cite
|
Sign up to set email alerts
|

Substrate specificity and proposed structure of the proofreading complex of T7 DNA polymerase

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 64 publications
1
12
0
Order By: Relevance
“…We began by choosing three RNA substrates on which to measure excision. Most proofreading exonucleases function on at least partially single-stranded nucleic acids arising from the melting of duplex DNA or RNA at the polymerase active site to transfer the 3′-end of the primer into the exonuclease active site. ,, Our data show that, unlike other proofreading exonucleases, neither single-stranded RNA nor double-stranded RNA containing a mismatch is a preferred substrate, exhibiting rates of hydrolysis 45- to 125-fold slower than rates of excision on correctly base-paired RNA. This observation may imply that the RNA duplex must dissociate completely from the polymerase active site and both strands of the RNA must rebind at the exonuclease active site without tethering the template strand in the polymerase active site, as previously suggested .…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…We began by choosing three RNA substrates on which to measure excision. Most proofreading exonucleases function on at least partially single-stranded nucleic acids arising from the melting of duplex DNA or RNA at the polymerase active site to transfer the 3′-end of the primer into the exonuclease active site. ,, Our data show that, unlike other proofreading exonucleases, neither single-stranded RNA nor double-stranded RNA containing a mismatch is a preferred substrate, exhibiting rates of hydrolysis 45- to 125-fold slower than rates of excision on correctly base-paired RNA. This observation may imply that the RNA duplex must dissociate completely from the polymerase active site and both strands of the RNA must rebind at the exonuclease active site without tethering the template strand in the polymerase active site, as previously suggested .…”
Section: Discussionmentioning
confidence: 79%
“…Double-stranded RNA containing either correctly base-paired or mispaired 3′-terminal primer strands represents RNA replication intermediates that would be continuously formed by the RdRp during genome replication and possibly excised by the exonuclease. For well-characterized proofreading exonucleases, single-stranded nucleic acids are the preferred substrates. , When primer extension at the polymerase active site stalls, the primer strand of duplex DNA can melt away from the complementary template strand and enter the exonuclease active site where the 3′-terminal base is rapidly excised …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, linear amplification methods, in which the product DNA cannot act as a substrate, have slower kinetics and limited sensitivity compared to exponential methods like PCR or MDA [ 7 ]. Linear amplification has been using in a single-cell sequencing technique to avoid bias introduced by PCR and increase sequencing accuracy [ 47 ]; however, Δ28 gp5 has a reduced fidelity relative to WT gp5 owing to the mutations in the proof-reading exonuclease domain [ 48 ]. A possibility is that the WT T7 replisome could be used with a non-specific nicking endonuclease, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…We then used this variant to characterize the conformational dynamics that govern correct nucleotide incorporation ( 9 ) and compared that with mismatched nucleotide incorporation ( 10 ) to define the mechanistic basis for the extraordinary fidelity of this enzyme. We also previously characterized the DNA substrate specificity for the proofreading exo of T7 DNA pol using rapid-quench methods and showed that the rate of mismatch excision increased with the single-stranded nature of the DNA substrate; that is, ssDNA was hydrolyzed the fastest, whereas the 3′-terminal base in duplex DNA was removed at a rate that increased with the number of mismatched base pairs ( 11 ). Surprisingly, we found that a mismatch buried by a single correct base pair was removed much more efficiently than a single terminal mismatch, demonstrating that the enzyme affords multiple opportunities to remove a mismatch.…”
mentioning
confidence: 99%